A qualitative inquiry of minimalistic mindset outcomes on Iranian English language teachers’ well-being - Mohammad Ghafouri; Jaleh Hassaskhah (Discover Psychology, 2024)
Abstract Language teaching is a tense occupation wherein countless negative stressors such as students’ misbehaviors, low income, assessment issues, and personal conflicts might threaten the well-being and happiness of teachers. Thus, cultivating a flexible mindset responsive enough to tackle various stressors has become a promising research scope. In this vein, minimalism, as a worldview that helps people reduce unwanted and excessive distractors, might be a possible solution that would possibly reduce the teachers’ life and occupation stressors and cultivate their well-being-related strengths. However, the concept has been ignored in educational domains. Therefore, the present exploratory study sheds light on the minimalistic mindset of 34 Iranian English language teachers, recruited through purposeful sampling method and partook in an interview. Their answers were analyzed through thematic analysis to see whether minimalistic mindsets of teachers contribute to their welfare or not. The analyses of the qualitative data signaled that the findings would contribute to the educational psychology and language education literature by suggesting that teachers with minimalistic worldviews towards life are less stressed and concerned about distractors and are more prone to value inner peace, tolerance, and rapport in their personal and professional life.